Chelating solid-phase extraction filler as well as preparation and application thereof

By covalently bonding orthophenolone chelating ligands on the surface of polymer microspheres, a new solid-phase extraction filler was prepared, which solved the problem of low separation efficiency and insufficient stability of uranium and lanthanides in the prior art, and achieved the effect of efficient separation of uranium and rare earth elements in strong acidic solutions.

CN119896879AActive Publication Date: 2025-04-29DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311409320.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-27
Publication Date
2025-04-29
Estimated Expiration
2043-10-27

AI Technical Summary

Technical Problem

The existing liquid-liquid extraction technology has problems such as low separation efficiency, low product purity, use of toxic solvents and generating a large amount of waste in the separation of uranium and lanthanides, and the stability and service life of the extracted resin are insufficient.

Method used

A covalently bonded solid-phase extraction filler based on orthophenolone chelating ligands was developed. The chelating ligand was bonded to the surface of polystyrene polymer microspheres through covalent bonding to form a new chelating solid-phase extraction filler, suitable for separation of uranium and rare earth elements in strong acidic solutions.

Benefits of technology

The filler exhibits good uranium adsorption properties and separation ability of rare earth elements in strong acidic solutions. It has the advantages of rapid separation, good selectivity and acid resistance stability. It is suitable for efficient treatment of spent fuel and removal of uranium in rare earth ores.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a novel chelating solid-phase extraction filler capable of being used for separating uranium from rare earth elements in a strong acid solution. The chelating solid-phase extraction filler is prepared by bonding a phenanthroline derivative chelating ligand to the surface of a polystyrene polymer microsphere through a covalent bonding method. The filler has a very good separation effect on uranium and rare earth elements in a strong acid solution, has relatively strong adsorption selectivity on uranium, and is particularly suitable for extraction and recovery of uranium in a strong acid spent fuel digestion solution and efficient separation of uranium and fission product lanthanide elements. The solid-phase extraction method based on the novel chelate ion solid-phase extraction filler has the advantages of being rapid in separation, good in selectivity, excellent in uranium adsorption effect in a strong acid environment and the like, and has good application potential in the fields of efficient treatment of spent fuel, burnup analysis and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a novel solid phase extraction filler and a preparation method thereof, in particular to a novel chelating solid phase extraction filler whose bonding phase is a chelating ligand. Background Art

[0002] The efficient separation of uranium and lanthanide elements has important application value in the nuclear industry and rare earth metallurgy. For example, in the recycling of spent fuel, it involves the complete separation of uranium and fission product rare earth elements in the spent fuel to achieve the recovery of uranium, and in the separation and purification process of rare earth metallurgy, it also involves the removal of trace uranium and thorium contained in the rare earth elements. At present, the most widely used separation method in the field of spent fuel disposal and recycling in rare earth metallurgy and nuclear industry is liquid-liquid extraction technology. Although the production cost of liquid-liquid extraction technology is low and suitable for large-scale production, its separation efficiency is low and the product purity is generally not high. In addition, there are some defects that cannot be ignored in its application in the field of radioactive material separation, such as the use of a large amount of toxic volatile organic solvents in the separation process, the hydrolysis and radiation degradation of extractants and solvents, the formation of the third phase in the extraction process, and the generation of a large amount of secondary radioactive waste.

[0003] In order to solve the defects of liquid-liquid extraction technology, researchers have developed a solid-phase extraction method based on leaching resin. Although the leaching resin separation technology has greatly improved the slow mass transfer rate and low separation efficiency of the liquid-liquid extraction method, since the extractant is immobilized on the solid substrate by physical coating or impregnation, the stability of the prepared solid-phase extraction material is poor, which in turn causes the material to have a short service life. On the other hand, since the leaching resin technology is essentially a liquid-liquid extraction technology, the mass transfer rate and stability of the leaching resin are still far behind those of the solid-phase extraction fillers prepared by covalent bonding.

[0004] Therefore, in view of the problems existing in the separation and purification methods of uranium and lanthanide elements, it is of great significance to develop a novel solid phase extraction filler with high efficiency, stability and low cost for the recovery of uranium and the removal of trace uranium in rare earth samples. In the present invention, we plan to prepare a covalently bonded solid phase extraction filler based on o-phenanthroline chelating ligands. Relying on the strong affinity of o-phenanthroline chelating ligands for actinides, we try to use this filler to separate uranium and rare earth elements in solutions of different acidity, providing new ideas for the research and development of solid phase extraction materials suitable for the separation of uranium and rare earth elements in strong acid solutions. Summary of the invention

[0005] The purpose of the present invention is to provide a novel solid phase extraction filler and a preparation method thereof. The solid phase extraction filler is a novel chelating solid phase extraction filler whose bonding phase is a phenanthroline derivative. The solid phase extraction filler has a good adsorption effect on uranium in a strongly acidic solution.

[0006] The technical solution of the present invention is: a chelating solid phase extraction filler, characterized in that the structure is:

[0007]

[0008] Wherein, PS is polystyrene-divinylbenzene-glycidyl methacrylate (PS-GMA) microspheres, n=0-8, m=0-10, X - It is one, two or three of chloride ion, bromide ion and iodide ion.

[0009] The present invention also provides a method for preparing the above-mentioned chelating solid phase extraction filler, which is characterized by comprising the following steps:

[0010] (1) Synthesis of 1,10-phenanthroline derivative chelating ligands:

[0011] ①Synthesis of chelating ligands of 1,10-phenanthroline derivatives: ①Add 1,10-phenanthroline-2,9-dicarboxylic acid to DMF and heat to 40-80°C. Then add N'N-carbonyldiimidazole (CDI) and react at 25-70°C for 2h. Then add compound 1 dropwise at 20°C-30°C, and then stir and react at room temperature for 1-5 days. After the reaction is completed, remove the reaction solvent by distillation under reduced pressure. Add 1-1.5mol / L Na2CO3 solution to the residue and place it at 0-10°C for 8-16 hours. The resulting precipitate is washed with water and ether and then dissolved in a mixed solvent. Filter the solution to remove insoluble impurities, and remove the solvent by rotary evaporation to obtain compound 2.

[0012] ② Compound 3 is dissolved in an organic solvent and then slowly added dropwise to the solution of compound 2 dissolved in the mixed solvent. Subsequently, the solution is stirred at 10-50°C for 6-24h and heated to 50-80°C for 1-4 days. Diisopropylethylamine is then added and stirred for 1-4h, followed by reduced pressure distillation to remove the solvent, and the residue is washed with a non-polar solvent. The resulting product is vacuum dried to obtain compound 4.

[0013] (2) Covalent modification of the chelating ligand on the surface of the polymer microspheres: Compound 4 was dissolved in a mixed solvent, and then the PS-GMA microspheres were dispersed in the solution. The mixture was reacted at 50-80°C with mechanical stirring for 12-36 hours, centrifuged, and washed in sequence to obtain a chelating solid phase extraction filler.

[0014] The structures of the above-mentioned compounds 1 and 2 are as follows:

[0015] Compound 1:

[0016]

[0017] Compound 2:

[0018]

[0019] Among them, m=0~10.

[0020] The structures of the above compounds 3 and 4 are as follows:

[0021] Compound 3:

[0022]

[0023] Compound 4:

[0024]

[0025] Wherein, n=0-8, m=0-10, and X is one, two, or three of chlorine, bromine, and iodine atoms.

[0026] Furthermore, the ratio of 1,10-phenanthroline-2,9-dicarboxylic acid to DMF in step (1)① is 1:10 to 1:50 (m / v, g / mL).

[0027] Furthermore, the ratio of 1,10-phenanthroline-2,9-dicarboxylic acid to N'N-carbonyldiimidazole in step (1)① is 1:1 to 1:5 (n / n, molar ratio).

[0028] Furthermore, in step (1)①, the ratio of 1,10-phenanthroline-2,9-dicarboxylic acid to compound 1 is 1:1 to 1:5 (n / n, molar ratio).

[0029] Furthermore, the ratio of 1 mol / L Na2CO3 to 1,10-phenanthroline-2,9-dicarboxylic acid in step (1)① is 10:1 to 100:1 (v / m, mL / g).

[0030] Furthermore, the mixed solvent in steps (1) ①, ② and step (2) is any two or more of methanol, ethanol, acetonitrile and acetone, and the volume content of each is at least 20%, wherein the amount ratio of the mixed solvent to compound 2 in step (1) ② is 20:1 to 100:1 (v / n, mL / mmol), and the amount ratio of the mixed solvent to compound 4 in step (2) is 5:1 to 100:1 (v / n, mL / mmol).

[0031] Furthermore, the organic solvent in step (1)② is one of methanol, ethanol, acetonitrile, acetone, and tetrahydrofuran, and the ratio of the organic solvent to compound 3 is 3:1 to 10:1 (v / m).

[0032] Furthermore, in step (1)②, the dosage ratio of compound 2 to compound 3 is 1:2 to 1:3 (n / n).

[0033] Furthermore, in step (1)②, the ratio of compound 3 to diisopropylethylamine is 1:1 to 1:3 (n / n).

[0034] Furthermore, the non-polar solvent in step (1)② is one or more of petroleum ether, cyclohexane, and n-hexane.

[0035] Furthermore, in step (2), the ratio of compound 4 to PS-GMA is 0.5-5 mmol of compound 4 per gram of PS-GMA.

[0036] The chelated solid phase extraction filler is prepared by bonding a type of o-phenanthroline derivative chelated ligand to the surface of polystyrene polymer microspheres by covalent bonding. This filler has a good separation effect on uranium and rare earth elements in a strong acid solution, has a strong adsorption selectivity for uranium, and is particularly suitable for the extraction and recovery of uranium in a strong acid spent fuel digestion solution and the efficient separation of uranium and fission product lanthanide elements. The solid phase extraction method based on the novel chelated ion solid phase extraction filler involved in the present invention has the advantages of fast separation, good selectivity, and excellent uranium adsorption effect in a strong acid environment, and has good application potential in the fields of efficient treatment of spent fuel and burnup analysis.

[0037] Beneficial effects:

[0038] Compared with the prior art, the present invention is characterized in that:

[0039] 1. The structure is novel. The present invention covalently bonds the o-phenanthroline derivative chelating ligand to the surface of the polymer microsphere, and the obtained filler has good structural stability and acid resistance stability.

[0040] 2. The filler prepared by the method of the present invention has excellent adsorption performance for uranium in acidic solution.

[0041] 3. The filler prepared by the method of the present invention has good separation ability for uranium and rare earth elements in acidic solution.

[0042] 4. This type of filler has great application potential and has high application value in the recovery of spent fuel and the removal of uranium from rare earth mines. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 Variation trend of adsorption rate of uranium and four rare earth elements by chelate solid phase extraction filler 1 with solution nitric acid concentration DETAILED DESCRIPTION

[0044] In order to make the purpose, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the examples. Several embodiments of the present invention are given in the examples. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thorough and comprehensive.

[0045] The preparation method of the chelating solid phase extraction filler has the following specific preparation steps:

[0046] 1. Preparation method of chelating solid phase extraction filler:

[0047] (1) Synthesis of 1,10-phenanthroline derivative chelating ligands:

[0048] ①Synthesis of chelating ligands of 1,10-phenanthroline derivatives: ①Add 1,10-phenanthroline-2,9-dicarboxylic acid to DMF and then heat to 40-80°C. Then add N'N-carbonyldiimidazole (CDI) and react at 25-70°C for 2h. Then add compound 1 dropwise at 20°C-30°C, and then stir and react at room temperature for 1-5 days. After the reaction is completed, remove the reaction solvent by distillation under reduced pressure. Add 1mol / L Na2CO3 solution to the residue and place it at 0-10°C for 8-16h. The resulting precipitate is washed with water and ether and then dissolved in a mixed solvent. Filter the solution to remove insoluble impurities, and remove the solvent by rotary evaporation to obtain compound 2.

[0049] The ratio of 1,10-phenanthroline-2,9-dicarboxylic acid to DMF is 1:10-1:50 (m / v, g / mL); the ratio of 1,10-phenanthroline-2,9-dicarboxylic acid to N'N-carbonyldiimidazole is 1:1-1:5 (n / n, molar ratio); the ratio of 1,10-phenanthroline-2,9-dicarboxylic acid to compound 1 is 1:1-1:5 (n / n, molar ratio). The ratio of 1-1.5 mol / L Na2CO3 to 1,10-phenanthroline-2,9-dicarboxylic acid is 10:1-100:1 (v / m, mL / g).

[0050] The mixed solvent used is any two or more of methanol, ethanol, acetonitrile and acetone, and the volume content of each is at least 20%.

[0051] The structures of the above-mentioned compound 1 and compound 2 are:

[0052] Compound 1:

[0053]

[0054] Compound 2:

[0055]

[0056] Among them, m=0~10.

[0057] ② Compound 3 is dissolved in an organic solvent and then slowly added dropwise to the solution of compound 2 dissolved in the mixed solvent. Subsequently, the solution is stirred at 10-50°C for 6-24h and heated to 50-80°C for 1-4 days. Diisopropylethylamine is then added and stirred for 1-4h, followed by reduced pressure distillation to remove the solvent, and the residue is washed with a non-polar solvent. The resulting product is vacuum dried to obtain compound 4.

[0058] Among them, the mixed solvent used is any two or more of methanol, ethanol, acetonitrile, and acetone, and the ratio of the mixed solvent to compound 2 is 20:1 to 100:1 (v / n, mL / mmol); the organic solvent used is one of methanol, ethanol, acetonitrile, acetone, and tetrahydrofuran, and the ratio of the organic solvent to compound 3 is 3:1 to 10:1 (v / m); the non-polar solvent used is one of petroleum ether, cyclohexane, and n-hexane.

[0059] The amount ratio of compound 2 to compound 3 is 1:2 to 1:3 (n / n), and the amount ratio of compound 3 to diisopropylethylamine is 1:1 to 1:3 (n / n).

[0060] The structures of the above compounds 3 and 4 are:

[0061] Compound 3:

[0062]

[0063] Compound 4:

[0064]

[0065] Wherein, n=0 to 8, m=0 to 10, and X is one of a chlorine atom, a bromine atom, and an iodine atom.

[0066] (2) Covalent modification of the chelating ligand on the surface of the polymer microspheres: Compound 4 was dissolved in a mixed solvent, and then PS-GMA was dispersed in the solution. The mixture was reacted at 50-80°C with mechanical stirring for 12-36 hours, centrifuged, and washed in sequence to obtain a chelating solid phase extraction filler.

[0067] The ratio of compound 4 to PS-GMA is 0.5-5 mmol of compound 4 per gram of PS-GMA.

[0068] Specific implementation

[0069] The content of the present invention and the positive effects brought about by the present invention will be explained with specific implementation methods below.

[0070] Example 1

[0071] (1) Synthesis of chelating ligands of 1,10-phenanthroline derivatives: ① Add 4.5 g (16.8 mmol) of 1,10-phenanthroline-2,9-dicarboxylic acid to 95 mL of DMF (it cannot be completely dissolved and is a milky yellow suspension), and then heat to 45°C. Then add 8.55 g (52.73 mmol) of CDI in 5 equal portions (foam appears on the surface of the solution during the addition process, and bubbles are released), and react at 45°C for 2 h. Then add 4.30 mL (36.0 mmol) of N-(3-aminopropyl)imidazole dropwise at 20°C, and then stir the reaction at room temperature for 4 days (the solution gradually turns transparent light brown during the addition process). After the reaction is completed, add 50 mL of water to the reaction solution and remove DMF by distillation under reduced pressure. 200 mL of 1 mol / L Na2CO3 was added to the residue and placed at 5°C overnight (12 h). The resulting precipitate was washed with water and ether in turn and dissolved in 50 mL of a mixed solvent of acetonitrile / ethanol (v / v=1 / 1). The solution was turbid yellow. The precipitate was removed by filtration to obtain a clear yellow solution. The solvent was removed by rotary evaporation to obtain a brown liquid. The solution was placed at 60°C overnight (12 h). The liquid solidified into a yellow-white solid, thus obtaining 2,9-bis(N-(1-imidazolyl)propylaminocarbonyl)-1,10-phenanthroline.

[0072] ② 2.34g (10.05mmol) of 4-bromo-butylamine hydrobromide was dissolved in 10mL of acetonitrile and then slowly added dropwise to 90mL of acetonitrile / ethanol (v / v=1 / 1) solution containing 2.0g (4.15mmol) of 2,9-di(N-(1-imidazolyl)propylaminocarbonyl)-1,10-phenanthroline. Subsequently, the solution was stirred at 20°C for 12h and reacted at 75°C for 2 days. Then 12mmol of diisopropylethylamine was added and stirred for 2h, followed by reduced pressure distillation to remove the solvent, and the residue was washed with n-hexane. The obtained product was vacuum dried and then used for the modification of polymer microspheres. The structure of the obtained product chelating ligand was confirmed by Q-TOF mass spectrometry, nuclear magnetic resonance hydrogen spectrum, and elemental analysis as shown below:

[0073]

[0074] The product was characterized in positive ion mode by Q-TOF mass spectrometry as [C 34 H 46 N 10 O2] 2+ The mass-to-charge ratio is m / z = 392.6084.

[0075] (2) Covalent modification of chelating ligands on the surface of polymer microspheres: 5 mmol of the product obtained in step ② was dissolved in a mixed solvent of 20 mL acetonitrile and 15 mL ethanol. Then, 2.5 g PS-GMA (polystyrene-divinylbenzene-glycidyl methacrylate, average particle size 70 μm, average pore size Specific surface area 250m 2 / g) were dispersed in the solution, reacted at 65°C for 24h under mechanical stirring, centrifuged, and washed with ethanol, water, and acetone in sequence to obtain a chelating solid phase extraction filler 1. The obtained chelating solid phase extraction filler 1 had an average particle size of 70 μm and an average pore size of The specific surface area is 230m 2 / g, and the bonding density of the chelating ligand was 0.03mmol / g. The obtained chelating solid phase extraction filler was characterized by elemental analysis and infrared spectrum, which proved that it was successfully prepared.

[0076] The epoxy resin filler PS-GMA used was prepared by the synthesis method described in the literature (D. Yuan, B. Huang / Catalysis Communications 18 (2012) 126-131).

[0077] Example 2

[0078] The difference from Example 1 is that an equal mole of 2-imidazole-1-ylethylamine is used instead of N-(3-aminopropyl)imidazole. Finally, a chelating solid phase extraction filler 2 is obtained, and its structural schematic diagram is as follows. The average particle size of the obtained chelating solid phase extraction filler 2 is 73 μm, and the average pore size is The specific surface area is 223m 2 / g, and the bonding density of the chelating ligand was 0.05mmol / g. The obtained chelating solid phase extraction filler 2 was characterized by elemental analysis and infrared spectrum, which proved that it was successfully prepared.

[0079]

[0080] Example 3

[0081] The difference from Example 2 is that 2-bromoethylamine hydrobromide is used in an equal molar amount instead of 4-bromo-butylamine hydrobromide. Finally, a chelating solid phase extraction filler 3 is obtained, and its structural schematic diagram is as follows. The average particle size of the obtained chelating solid phase extraction filler 3 is 68 μm, and the average pore size is The specific surface area is 246m 2 / g, and the bonding density of the chelating ligand was 0.03mmol / g. The obtained chelating solid phase extraction filler 3 was characterized by elemental analysis and infrared spectrum, which proved that it was successfully prepared.

[0082]

[0083] Example 4

[0084] The difference from Example 1 is that 6-bromo-hexylamine hydrobromide is used in an equal molar amount instead of 4-bromo-butylamine hydrobromide. Finally, a chelating solid phase extraction filler 4 is obtained, and its structural schematic diagram is as follows. The average particle size of the obtained chelating solid phase extraction filler 4 is 71 μm, and the average pore size is The specific surface area is 231m 2 / g, and the bonding density of the chelating ligand was 0.02mmol / g. The obtained chelating solid phase extraction filler 4 was characterized by elemental analysis and infrared spectrum, which proved that it was successfully prepared.

[0085]

[0086] Example 5

[0087] The adsorption performance of chelate solid phase extraction filler 1 on uranium and lanthanide elements in solutions of different acidity was tested, including the following steps:

[0088] First, a series of mixed aqueous solutions with different nitric acid concentrations (0.005, 0.025, 0.050, 0.250, 0.500, 1.000, 1.500 mol / L) were prepared, all of which contained the same concentration of uranium (47.6 mg / L) and four rare earth element solutions (La, 43.6 mg / L; Sm, 34.2 mg / L; Yb, 47.9 mg / L; Y, 22.6 mg / L). 20 mL of each solution with different nitric acid concentrations was taken, and then 10 mg of the chelated solid phase extraction filler 1 prepared in Example 1 was added. After uniform dispersion, the mixture was shaken and adsorbed in a rotary incubator for 2 h. After the adsorption was completed, the mixture was allowed to stand for 10 min, 2 mL of the supernatant was taken into a centrifuge tube, and the residual rare earth element content in the supernatant was determined using ICP-MS, and then the adsorption efficiency of the chelated solid phase extraction filler 1 on uranium and four rare earth element solutions in solutions containing different nitric acid concentrations was calculated. The variation trend of the adsorption efficiency and the nitric acid concentration is shown in FIG. Figure 1 As shown. The adsorption rate of chelating solid phase extraction filler for rare earth elements and uranium = (rare earth element concentration in the initial solution - rare earth element concentration in the supernatant after adsorption) ÷ rare earth element concentration in the initial solution

[0089] from Figure 1 It can be seen that the adsorption capacity of the four rare earth elements on the chelate solid phase extraction filler 1 tends to weaken with the increase of nitric acid concentration in the sample solution, while the adsorption capacity of the chelate solid phase extraction filler 1 for UO2 2+ The adsorption capacity of the chelating solid phase extraction filler is gradually enhanced with the increase of acid concentration. When the nitric acid concentration in the solution reaches 1.500 mol / L, the adsorption capacity of the chelating solid phase extraction filler is 1 to UO2 2+ The adsorption rate can reach over 91%.

[0090] Example 6

[0091] In the solid phase extraction mode, the adsorption performance test of uranium in the simulated reactor spent fuel by the chelating solid phase extraction filler 1 includes the following steps:

[0092] First, the chelate solid phase extraction filler 1 prepared by embodiment 1 of 0.5g is loaded into 3mL SPE column tube (internal diameter 5.6mm, length 56.5mm), then use water to wash 10mL, then use 2M nitric acid solution 0.5mL / min balance solid phase column 30min, take 0.2mL respectively containing 1mol / L and 2mol / L nitric acid respectively simulated spent fuel digestion solution (component composition is as shown in table 1) solid phase column is loaded, sample flow rate is 0.2mL / min, then use nitric acid solution of same concentrations to rinse column 10mL respectively, collect effluent, uranium content is detected wherein. The adsorption effect of chelate solid phase extraction filler 1 on uranium in simulated reactor spent fuel is as shown in table 2.

[0093] Table 1 Content of each element in simulated light water reactor spent fuel

[0094]

[0095] Table 2 Adsorption effect of chelated solid phase extraction filler 1 on uranium in simulated reactor spent fuel with different acidities

[0096]

[0097] The adsorption rate of uranium by chelating solid phase extraction filler = (U content in simulated spent fuel sample solution - U content in effluent solution) ÷ U content in simulated spent fuel sample solution

[0098] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0099] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a chelating solid phase extraction filler, characterized in that: include: The structure of the chelating solid phase extraction filler is shown below: Wherein, PS is polystyrene-divinylbenzene-glycidyl methacrylate (PS-GMA) microspheres, n=0-8 (preferably 1-3), m=0-10 (preferably 1-5), X - It is one, two or three of chloride ion, bromide ion and iodide ion; The preparation method of the chelating solid phase extraction filler is characterized by comprising the following steps: (1) Synthesis of 1,10-phenanthroline derivative chelating ligands: ① Synthesis of chelating ligands of 1,10-phenanthroline derivatives: ① Add 1,10-phenanthroline-2,9-dicarboxylic acid to DMF, and then heat to 40-80°C; then add N'N-carbonyldiimidazole (CDI) and react at 25-70°C for 1-4h (preferably 2-3h); then add compound 1 dropwise at 20-30°C, and then stir and react at room temperature for 1-5 days (preferably 1-2 days); after the reaction is completed, remove the reaction solvent by distillation under reduced pressure; add 1-1.5 mol / L Na2CO3 solution to the residue, and place it at 0-10°C for 8-16h (preferably 10-12h), wash the resulting precipitate with water and ether in turn, and then dissolve it with a mixed solvent, filter the solution to remove insoluble impurities, and remove the solvent by rotary evaporation to obtain compound 2; ② Compound 3 is dissolved in an organic solvent, and then added dropwise to a solution of compound 2 dissolved in a mixed solvent; subsequently, the solution is stirred at 10-50° C. for 6-24 h, and the temperature is raised to 50-80° C. (preferably 60-70° C.) for reaction for 1-4 days (preferably 1-2 days); then diisopropylethylamine is added and stirred for 1-4 h (preferably 2-3 h), and then the solvent is removed by distillation under reduced pressure, and the residue is washed with a non-polar solvent; the obtained product is vacuum dried to obtain compound 4; (2) Covalent modification of the chelating ligand on the surface of the polymer microspheres: Compound 4 is dissolved in a mixed solvent, and then the PS-GMA microspheres are dispersed in the solution. The reaction is carried out under mechanical stirring at 50-80°C (preferably 60-70°C) for 12-36h (preferably 18-24h), centrifuged, and washed in sequence to obtain a chelating solid phase extraction filler. The structures of compound 1 and compound 2 are as follows: Compound 1: Compound 2: Wherein, m=0 to 10 (preferably 0 to 3); The structures of compound 3 and compound 4 are as follows: Compound 3: Compound 4: Among them, n=0-8 (preferably 1-3), m=0-10 (preferably 0-3), and X is one, two, or three of a chlorine atom, a bromine atom, and an iodine atom.

2. The method according to claim 1, characterized in that: The amount ratio of 1,10-phenanthroline-2,9-dicarboxylic acid to DMF (N,N-dimethylformamide) described in step (1) ① is 1:10 to 1:50 (m / v, g / mL) (preferably 1:20 to 1:30), and the amount ratio of 1,10-phenanthroline-2,9-dicarboxylic acid to N'N-carbonyldiimidazole is 1:1 to 1:5 (n / n, molar ratio) (preferably 1:2 to 1:3); The ratio of 1,10-phenanthroline-2,9-dicarboxylic acid to compound 1 is 1:1 to 1:5 (n / n, molar ratio), (preferably 1:2 to 1:3); The ratio of the amount of the 1-1.5 mol / L Na2CO3 solution used in step (1)① to the amount of 1,10-phenanthroline-2,9-dicarboxylic acid used is 10:1 to 100:1 (v / m, mL / g) (preferably 20:1 to 50:1).

3. The method according to claim 1, characterized in that: The particle size of the polystyrene-divinylbenzene-glycidyl methacrylate (PS-GMA) microspheres is 40 to 100 μm (preferably 50 to 80 μm), and the pore size is (Preferred ), the specific surface area is 100~500m 2 / g (preferably 200-300m 2 / g), chelating functional group density 0.01-0.1mmol / g (preferably 0.02-0.08mmol / g).

4. The method according to claim 1, characterized in that: The mixed solvent described in steps (1) ①, ② and step (2) is any two or more of methanol, ethanol, acetonitrile and acetone, and the volume content of each is at least 20%, wherein the amount ratio of the mixed solvent to compound 2 in step (1) ② is 20:1 to 100:1 (v / n, mL / mmol) (preferably 50:1 to 80:1), and the amount ratio of the mixed solvent to compound 4 in step (2) is 5:1 to 100:1 (v / n, mL / mmol) (preferably 10:1 to 30:1).

5. The method according to claim 1, characterized in that: The organic solvent described in step (1) ② is one of methanol, ethanol, acetonitrile, acetone, and tetrahydrofuran, and the amount ratio of the organic solvent to compound 3 is 3:1 to 10:1 (v / m, mL / g).

6. The method according to claim 1, characterized in that: The ratio of compound 2 to compound 3 in step (1) ② is 1:2 to 1:3 (n / n) (preferably 1:2.1 to 1:2.5); The amount ratio of compound 3 and diisopropylethylamine in step (1) ② is 1:1 to 1:3 (n / n) (preferably 1:1.8 to 1:2.2).

7. The method according to claim 1, characterized in that: The non-polar solvent in step (1) ② is one or more of petroleum ether, cyclohexane and n-hexane; The ratio of compound 4 to PS-GMA in step (2) is 0.5-5 mmol (preferably 1.5-2.5 mmol) of compound 4 per gram of PS-GMA.

8. A chelating solid phase extraction filler prepared by the method according to any one of claims 1 to 7.

9. A chelated solid phase extraction filler as claimed in claim 8 for separation of uranium and rare earth elements in an acidic solution.

10. Use of the chelated solid phase extraction filler according to claim 8 in a uranium adsorption process in reactor spent fuel digestion solution.

Citation Information

Patent Citations

  • Functional polymer microsphere, synthesis preparation method and application thereof

    CN105906759A

  • Magnetic adsorbent as well as preparation thereof and treatment method to actinide element waste liquid

    CN109317117A

  • Porous amidoxime polymer microsphere, preparation and application in uranyl ion adsorption

    CN116218017A

  • Method for the preparation of controlled porosity supports for chromatographic separation

    US20210121866A1

  • Superficially porous materials comprising a substantially nonporous hybrid core having narrow particle size distribution; process for the preparation thereof; and use thereof for chromatographic separations

    WO2012018596A2